Exploring Indonesian Vocational Students’ Perspectives on Deep Learning in English Language Education - Tri Wintolo Apoko; Herni Setyawati; Anisah Assaadah; Dian Kusumawaty; Lifia Arif Parameswari (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2025)
The potential of deep learning in the context of English teaching is essential so as to increase student engagement and learning outcomes through some innovative learning models. However, few studies address the effect of deep learning in English classrooms from vocational high school students’ perspectives, mainly in Indonesian context. This study aims to disclose the students’ perceptions on the implementation of deep learning at vocational high schools, considering quantitative and qualitative data. The participants of this study are 191 students from four vocational high schools in Eastern Jakarta, Indonesia. The study employed a mixed-methods design, combining quantitative and qualitative data. The data were collected through an online questionnaire, comprising closed and open-ended questions. The data were then analyzed with descriptive statistics and thematic analysis. The results show that students have positive responses on their mindfulness, meaningfulness, and the enjoyment in English language teaching. Qualitatively, students found English very important for their career and considered the learning materials provided by English teachers relevant. Additionally, the students felt motivated to learn English for the enhancement of creative and critical thinking. This study recommends refining deep learning practices for effective and meaningful English learning environments.